Uncategorized

Solution: Solve the differential equation: x(y – 1) dx + (x + 1) dy = 0. If y = 2 when x = 1.

Solve the differential equation: x(y – 1) dx + (x + 1) dy = 0. If y = 2 when x = 1.

Problem Statement:

Solve the differential equation: x(y – 1) dx + (x + 1) dy = 0. If y = 2 when x = 1.

  • A. 1.80
  • B. 1.48
  • C. 1.55
  • D. 1.63

Problem Answer:

y is equal to 1.55

Solution:

Latest Problem Solving in Differential Equations

div.feedburnerFeedBlock ul li {background: #E2F0FD;
list-style-type: none;
margin:0 0 5px 0px;
padding:5px 5px 5px 10px !important;
border: 1px solid #0080ff;
border-radius:8px;
-moz-border-radius:8px;
-webkit-border-radius:8px;

}

div.feedburnerFeedBlock ul li:hover {
background:#ffffff;
}

div.feedburnerFeedBlock ul li a{
color:#ffffff;
text-decoration:none;
}

div.feedburnerFeedBlock ul li a:hover {
text-decoration: underline;
color: #000000;
}
div #creditfooter{
display: none;
}

More Questions in: Differential Equations

Online Questions and Answers in Differential Equations

Leave a Reply

Your email address will not be published. Required fields are marked *